Ranitidine reduced levodopa-induced dyskinesia by remodeling neurochemical changes in hemiparkinsonian model of rats - Shi H (Dove Medical Press, 2015)
Hongjuan Shi,1,2,* Xinxin Yang,2,3,* Hui Zhao,4 Shenyang Zhang,2 Jie Zu,2 Wei Zhang,2 Xia Shen,2 Guiyun Cui,2,3 Fang Hua,2,3 Chuanzhu Yan1 1Department of Neurology, Qilu Hospital of Shangdong University, Jinan, 2Department of Neurology, Affiliated Hospital of Xuzhou Medical College, 3Institute of Neurological Diseases of Xuzhou Medical College, 4Department of Neurology, Xuzhou Central Hospital, Xuzhou, People’s Republic of China *These authors contributed equally to this work Background: Levodopa (L-dopa) remains the best drug in the treatment of Parkinson’s disease (PD). Unfortunately, long-term L-dopa caused motor complications, one of which is L-dopa-induced dyskinesia (LID). The precise mechanisms of LID are not fully understood. We have previously reported that ranitidine could reduce LID by inhibiting the activity of protein kinase A pathway in a rat model of PD. It is demonstrated that neurotransmitters such as γ-aminobutyric-acid (GABA) and glutamate (Glu) are also involved in the expression of LID. But whether ranitidine could reduce LID by remodeling the neurochemical changes is unknown. Methods: In the present study, we produced PD rats by injection of 6-hydroxydopamine. Then PD rats were treated with vehicle, L-dopa (6 mg/kg, plus benserazide 12 mg/kg, intraperitoneal [ip]) or L-dopa (6 mg/kg, plus benserazide 12 mg/kg, ip) plus ranitidine (10 mg/kg, oral). Abnormal voluntary movements were adopted to measure the antidyskinetic effect of ranitidine in PD rats. Rotarod tests were used to observe whether ranitidine treatment affects the antiparkinsonian effect of L-dopa. In vivo microdialysis was used to measure nigral GABA and striatal Glu in PD rats. Results: We found that ranitidine pretreatment reduced abnormal voluntary movements in L-dopa-primed PD rats without affecting the antiparkinsonian effect of L-dopa. In parallel with behavioral improvement, ranitidine pretreatment reduced protein kinase A activity and suppressed the surge of nigral GABA and striatal Glu. Conclusion: These data indicated that ranitidine could reduce LID by modeling neurochemical changes induced by L-dopa, suggesting a novel mechanism of ranitidine in the treatment of LID. Keywords: ranitidine, Parkinson’s disease, levodopa-induced dyskinesia, PKA, γ-aminobutyric-acid, glutamate